Speed of thought and speed of feet: examining perceptual-cognitive expertise and physical performance in an english football academy - Kelly, A. L.; Wilson, M. R.; Jackson, D. T.; Turnnidge, J.; Williams, C. A. (Journal of Science in Sport and Exercise, 2021)
The world`s greatest professional football players are able to execute effective tactical decisions as well as fulfil various physical demands. However, the degree to which both are associated with greater potential in a football academy is unknown. Therefore, the aim of this study was to investigate decision-making skill and physical performance as contributing factors to coach potential rankings in an English football academy. Ninety-eight outfield academy players (Foundation Development Phase [FDP] under-9 to under-11 n = 40; Youth Development Phase [YDP] under-12 to under-16 n = 58) participated in the study. They engaged in 45 film-based simulations at two occlusion phases (e.g., the visual display is cut-off at a precise time during an action), firstly "during" and secondly "post" execution, to examine decision-making skill. Participants also completed four fitness tests to examine physical performance. A classification of "higher-potentials" (top third) and "lower-potentials" (bottom third) were applied through coach rankings. Independent t-tests compared the decision-making and physical performance tests. Higher-potentials made significantly more accurate decisions within the "post" phase within the FDP (P < 0.05) and the "during" phase within the YDP (P < 0.05). Additionally, higher-potentials were significantly faster for the 0-30 m sprint in both the FDP and YDP (P < 0.05), with higher-potentials within the YDP also significantly faster in the 0-10 m sprint (P < 0.05) and jumped significantly higher in the countermovement jump (P < 0.05). These findings indicated that greater football potential may be associated with superior perceptual-cognitive expertise and quicker sprint ability in both academy age phases, with a greater discriminatory function within the older cohort.